Validation of quikSCAT radiometer rain rates using the TRMM microwave radiometer - Kasparis, Takis; Jones, Wilma L.; Ahmad, Khalil A. (My University, 2002)
The primary mission of the SeaWinds scatterometer on the QuikSCAT satellite is to infer surface wind vector from ocean backscatter measurements. Occasionally the backscatter measurements are contaminated by the presence of rain; therefore a reliable method of identifying rain is needed. Fortunately, the SeaWinds scatterometer simultaneously obtains active (scattering) and passive (emission) measurements of the ocean; thus, the QuikSCAT Radiometer (QRad) measured brightness temperatures can be used to infer rain within the scatterometer antenna field-of-view. This paper describes a new QuikSCAT Level-2B science product of rain rate over oceans. The principal use of this product for quality control purposes to provide a quantitative rain flag associated with QuikSCAT wind vector cells. The QRad rain rate algorithm is described and the characteristics of the rain rates product are presented. This product has been validated by near-simultaneous comparisons with rain rate measurements from the Tropical Rainfall Measuring Mission (TRMM) Microwave Imager (TMI). An example of QuikSCAT retrieved winds in the presence of rain is presented with collocated QRad rain measurements. Results demonstrate that the QRad rain rate product provides a reliable, quantitative wind vector quality flag.
Keywords: Electromagnetic waves; Algorithms; Antennas (Electronics); Oceanography; Backscattering; Remote sensing